Caribbean: one and divisible - Casimir, Jean (ECLAC SantiagoCL, 1992)
Analyzes the creole. Examines the type of workers that succeed the slaves and shows how they differed from the wage-earning worker. Analyses the structure of regional unity based on the bahaviour patterns of the human groups involved. Outlines the progress of the various forms of consensus and identifies the local institutions that seem to underpin the social cohesion of the nation. Deals with the reproduction of structural dualism, despite a better integration of systems of production. Posits the existance of two civil societies and concludes with an analysis of the relationship between systems of government and the national culture.